BERPIKIR PSEUDO PADA MATERI STATISTIKA DASAR - Stevi Natalia (Jurnal Dinamika Pendidikan, 2020)
This study aims to make observations about the pseudo thinking process in mathematics education students before taking the Basic Statistics course. The method used in this study uses qualitative research methods in the form of case studies in five second semester students. In this study it was found that the five students experienced pseudo thinking. Three of them experienced true pseudo thinking and two of them experienced true pseudo thinking at the beginning but through instructions could find the correct concept. Students who experience true pseudo thinking process are still able to work on the given problem but are unable to understand the concept so that they are unable to implement the use of the material learned in different case examples including in everyday life. This is caused by many factors including, the understanding of concepts that are true and intact, teaching methods and making questions that support the occurrence of pseudo thinking processes. Keywords: Asimilation, Pseudo Thinking, Schema